Speaking of sadness: depression, disconnection and the meaning of illness - Nicholas Procter (AOSIS, 1997)
In recent years there has been a steady accumulation of published literature on mental health care for people with serious psychiatric illness. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.